Barb the last Berzerker. Book 2, Barb and the ghost blade - Abdo, Dan; Jason (Jason Linwood Patterson) (New York : Simon & Schuster Books for Young Readers, 2022)
Barb and her best friend Porkchop the yeti must save her fellow warriors from the evil sorcerer Witch Head before he destroys the land of Bailiwick.
School Library Journal starred, May 2022
3.1
3-6
Keywords: Yeti -- Comic books, strips, etc. -- Juvenile fiction; Monsters -- Comic books, strips, etc. -- Juvenile fiction; Wizards -- Comic books, strips, etc. -- Juvenile fiction; Swords -- Comic books, strips, etc. -- Juvenile fiction; Yeti -- Fiction; Monsters -- Fiction; Wizards -- Fiction; Swords -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Action and adventure comics; Fantasy comics; Graphic novels; Comics (Graphic works)